Molecular characterisation and expression analysis of an interferon-induced protein with tetratricopeptide repeats 1 (IFIT1) homologue from Asian seabass (Lates calcarifer) - Krishnapriya Raji Sathyan; Avinash Premraj; Sajeevan Thavarool Puthiyedathu (Comparative Immunology Reports)
The interferon-induced protein with tetratricopeptide repeats 1(IFIT1) is an interferon-inducible protein that acts downstream of the interferon pathway in response to viral infection or an interferon-stimulation. Our study describes the isolation and characterization of an IFIT1 homologue from Lates calcarifer (named LcIFIT1), as well as its expression profile in response to viral mimetic poly(I:C) and Red-spotted grouper nervous necrosis virus (RGNNV). The complete ORF of LcIFIT1 encodes a 441 amino acid protein with nine tetratricopeptide repeat (TPR) domains. The protein-coding region of the LcIFIT1 gene was encoded by two exons separated by a small 157 bp intron. The phylogenetic analysis revealed that LcIFIT1 is evolutionarily conserved and forms a distinct clade with homologues from other teleosts. LcIFIT1 mRNA was constitutively expressed in all tissues examined, with predominant expression in blood. LcIFIT1 expression was upregulated following poly(I:C) and RGNNV challenges in different tissues examined. These results shed light on the antiviral role of LcIFIT1 in the host immune response against nodaviral infection.